Energy and exergy analyses of a novel photoelectrochemical hydrogen production system - Acar, Canan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, we thermodynamically analyze and experimentally investigate a continuous type hybrid photoelectrochemical H-2 generation reactor. This system enhances solar spectrum use by employing photocatalysis and PV/T. Additionally, by replacing electron donors with electrodes to drive the photocatalysis, the potential of pollutant emissions are minimized. In this study, the present reactor is tested under electrolysis operation during which the present reactor is investigated under four operating temperatures, namely 20, 40, 60, and 80 degrees C. The present experimental results are compared to the thermodynamic model outputs. The parametric studies are undertaken by varying the operating temperature between 0 degrees C and 100 degrees C. The present experimental results show that the highest hydrogen production rate is observed at 80 degrees C with 0.79 mg/h. The highest energy and exergy efficiencies are calculated at 20 degrees C to be 36% and 32%, respectively. In addition, the present thermodynamic modeling results are compared to have a good agreement with the experimental results. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Energy; Exergy; Hydrogen production; Photoelectrochemical; Sustainability; Solar energy; P-TYPE CU2O; H-2 EVOLUTION; WATER; PHOTOCATALYST; MEMBRANE; DESIGN; Chemistry; Electrochemistry; Energy & Fuels